Phenological growth and development stages of common fig (Ficus carica L.) under arid climate of India - Singh Akath; Kishore Kundan; Kumar Pradeep; Khapte P. S.; Mishra D. S.; Singh Dalpat; Kothyari Hukam Singh (Folia Horticulturae, 2023)
Arid region is characterised by extreme climatic condition, poor soil health and over-exploitation of natural resources. Under prevailing conditions of arid India, Ficus carica is an emerging fruit crop with high commercial value and nutritional significance. Phenological study plays an important role in ensuring efficient crop management practices, but such studies in fig have not yet been conducted in India. The present study was conducted with an aim to define and describe phenological stages of common fig cultivar ‘Diana’ in arid regions according to the Biologische Bundesanstalt, Bundessortenamt und Chemische Industrie (BBCH)-scale using two-digit numerical system. The BBCH scale markedly explains various developmental stages of crops. Seven principal growth stages, viz. bud development (0), leaf development (1), shoot development (3), inflorescence development (5), flower development (6), syconium (fig receptacle) development (7) and fruit maturation (8), and 25 secondary growth stages of fig have been described. The sequential progression of principal growth stages of fig indicated temporal variation in growth pattern as well as overlapping of secondary growth stages. Phenological description will act as a pragmatic approach to define growth stages in order to facilitate timely agronomic practices such as canopy management, nutrient management and irrigation scheduling, pest and disease management. Since fig is considered one of the important minor fruits of India, a detailed phenological description will be instrumental in enhancing its potential in arid and semi-arid regions.